2021
DOI: 10.1016/j.ijnsa.2021.100031
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Covid-19-related distancing on the well-being of nursing home residents and their family members: a qualitative study

Abstract: Objectives: The aim of this study is to examine the consequences of Covid-19-related isolation and social restrictions on the well-being of nursing home residents and their family members, and to analyze how distancing has affected the relationships of family members with residents and the nursing home staff. Design: The data consist of 41 thematic one-on-one interviews conducted during May–December 2020 with family members of nursing home residents. Convenience sampling was utilized by asking sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 62 publications
5
56
0
Order By: Relevance
“…Thus, many authors have highlighted the importance of reintroducing visitors into CHs as soon as it is safe to do so [ 40 , 58 , 107 ], with calls for CHs to take a more flexible, risk-assessment-based approach to visits [ 38 , 67 ]. The urgency of this is accentuated by evidence emerging about the negative impacts of visiting restrictions on the physical, psychological, emotional and cognitive well-being of residents and their families and friends [ 174 , 175 ]. These findings resonate with other studies for nursing home residents [ 168 ], where restrictions resulted in several losses related to freedom, social contact, activities, communication and autonomy, and with residents describing feelings of depression, hopelessness, uselessness, and sadness.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, many authors have highlighted the importance of reintroducing visitors into CHs as soon as it is safe to do so [ 40 , 58 , 107 ], with calls for CHs to take a more flexible, risk-assessment-based approach to visits [ 38 , 67 ]. The urgency of this is accentuated by evidence emerging about the negative impacts of visiting restrictions on the physical, psychological, emotional and cognitive well-being of residents and their families and friends [ 174 , 175 ]. These findings resonate with other studies for nursing home residents [ 168 ], where restrictions resulted in several losses related to freedom, social contact, activities, communication and autonomy, and with residents describing feelings of depression, hopelessness, uselessness, and sadness.…”
Section: Discussionmentioning
confidence: 99%
“…25 Testing, isolation of residents, PPE, and staff and residents’ well-being were identified as challenges and dilemmas related to COVID-19 in care homes. 26 Remarkably, ample research has shown that COVID-19-related measures negatively impact nursing home residents’ mental and physical well-being, 4 but only little has been described about this in the meeting documents. Apparently, either OT meetings have a different focus, or OTs discuss well-being of residents but regard this as context to decisions that does not have to be written down in the minutes.…”
Section: Discussionmentioning
confidence: 99%
“…3 Besides, COVID-19-related measures negatively impact nursing home residents’ mental and physical well-being. 4 …”
Section: Introductionmentioning
confidence: 99%
“…The past two years have seen strict visitation restrictions at care homes around the world due to COVID-19 infection prevention measures and studies report increased levels of loneliness, stress, and depression among care home residents [23][24][25][26][27]. For months at a time in many locations, care home residents have not been able to meet with their spouses or their children, or meetings have been restricted to brief exchanges through a window or doorway.…”
Section: Introductionmentioning
confidence: 99%